Factors affecting decreased walking ability in patients with conservatively treated fragility fracture of the pelvic ring - Yasuo Kokubo; Hideaki Nakajima; Yuya Izubuchi; Akihiko Matsumine (Journal of Orthopaedics, Trauma and Rehabilitation)
Background: The clinical results of conservative treatment in correctly selected patients with fragility fracture of the pelvis are acceptable. However, there is a loss of social and physical independence and autonomy. This study aimed to evaluate factors associated with decreased walking ability in patients with conservatively treated fragility fractures of the pelvis. Methods: Overall, 124 patients aged >70 years were included. Fragility fracture of the pelvis was classified according to the Rommens classification. Walking ability before and 1 year after injury was assessed using the Functional Ambulation Category. Results: The overall recovery rate of walking ability of conservatively treated patients to the preinjury state was 73%, one year after injury. The presence of cancer and > four-week bed rest were determinants of decreased walking ability one year after injury. Conclusions: The presence of cancer and more than four-week bed rest were risk factors for a significant decrease in walking ability.